Statewide Appeal of a Gardening Packet - Mark A Claesgens (Journal of Applied Communications, 1984)
The Information Department print media writers in the Washington State University College of Agriculture and Home Economics prepared and distributed a packet of gardening information in 1983 for all weekly and selected dailies in the state.